Sosialisasi PHBS di Desa Kumantan - Aswara, Dana; Rahmadtulloh, Ismail; Saputra, Ardho (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2022)
This socialization activity was carried out to increase public awareness of Kumantan Village regarding the implementation of PHBS. The activity was carried out through lectures, leaflet distribution, and demonstrations of clean living practices. The problems faced include low public understanding of the importance of maintaining personal and environmental hygiene, limited basic sanitation facilities such as healthy toilets and hand washing places, and low access to health education. The implementation method was carried out through a participatory educational approach, involving the village government, health cadres, and the local community. Activities included initial observation, direct counseling, group discussions, and hand washing practices with soap. The results of the activity showed an increase in public knowledge about PHBS, as well as the emergence of changes in behavior towards a healthier direction, such as starting to throw garbage in its place and washing hands before eating. The success of this activity was supported by the active involvement of the village government and health cadres who carried out ongoing monitoring. The obstacles faced were limited sanitation facilities and the need for further training for cadres. However, this activity showed that an approach involving local communities is effective in increasing the implementation of PHBS in rural areas.